Adverse effect of vaccination in xenogeneic animals. (May 2022) - Shoulah, Salma A.; Elshafae, Said M.; Gaballa, Mohamed M.S.; Moussa, Maha A.; Selim, Abdelfattah; Attia, Kotb; AlKahtani, Muneera D.F.; Albohairy, Fatima M.
Abstract: Lumpy skin disease (LSD) is a devastating, emerging viral disease of cattle. It causes significant economic losses due to trade restrictions that are placed on infected animals and the biological effects of the disease: infertility, dramatic loss in milk production, induction of abortion and mortality. It is caused by lumpy skin disease virus (LSDV), which belongs to the Poxviridae family. Vaccination has been determined to be the most effective way to control LSD infection among livestock. However, some adverse effects have been reported in animals vaccinated with live vaccines. To the best of our knowledge, this is the first study to report the systemic lesions that are associated with LSD vaccination in xenogeneic animals. The aim of our study was to compare the immunogenicity and pathogenicity of a live attenuated vaccine of Romanian strain of sheeppox virus (SPPV) through study of two different routes of administration in xenogeneic animals (mice). Swiss male mice were inoculated with two doses of SPPV vaccine by two different routes intranasal (IN, through nebulisation), and intraperitoneal (IP) injection) and the levels of immunoglobulins and histopathological findings were reported. Our results showed marked increases in levels of immunoglobulins (Ig) dependent on the administration route: IgG in IP-inoculated mice and IgA in IN-vaccinated mice. IgM levels became markedly high after vaccination via both routes. Histologically, nebulisation of mice with SPPV vaccine caused more pulmonary lesions than did IP injection and promoted the proliferation of megakaryocytes in splenic tissues. In contrast, IP injection had less effect on pulmonary tissues and induced activation of extramedullary haematopoiesis (EH) in the hepatic tissues. LSD vaccination in xenogeneic animals caused serious systemic complications and the severity of the lesions caused to tissue depended on the route of administration. Highlights: Lumpy skin disease is chronic infectious disease of cattle and vaccination is best way to control it. Nebulisation of mice with sheeppox virus vaccine caused more pulmonary lesions than did intraperitoneal injection.